Hubungan Lama Menderita dan Self Esteem dengan Resiliensi Pasca Stroke - Sulisatul Isna Zuliani; Suyanto Suyanto; Retno Setyawati (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Stroke is a medical condition that can significantly affect patients' quality of life, both physically and psychologically. Decreased self-esteem and resilience are often experienced by post-stroke patients, which can worsen their recovery process. This study aims to examine the relationship between stroke duration and self-esteem with post-stroke resilience in patients at Sultan Agung Islamic Hospital Semarang. The research method used was a quantitative approach with a cross-sectional design. The study sample consisted of 80 stroke patients selected using accidental sampling technique. Data were collected through questionnaires measuring the length of stroke, self-esteem with Rosenberg Self-esteem Scale, and resilience with Connor-Davidson Resilience Scale (CD-RISC). The results showed that there was a significant relationship between stroke duration and post-stroke resilience (p<0.05), as well as a significant relationship between self-esteem and resilience (p<0.05). The implication of these findings is the importance of attention to psychological factors, particularly self-esteem, in the care of stroke patients, to support increased resilience and accelerate their recovery. This study provides a basis for the development of more holistic interventions in the rehabilitation of stroke patients, which include both physical and psychological aspects.